Hubungan Faktor Lingkungan, Sosial Ekonomi Dan Pemukiman Dengan Kejadian Tuberkulosis Di Wilayah Kerja Puskesmas Karya Wanita Kota Pekanbaru Tahun 2026 - Desi Susanti; Herniwanti Herniwanti; Sri Irianti; Yessi Harnani; Kamali Zaman; Iswadi Iswadi (Science and Education Journal (SICEDU), 2026)
Tuberculosis (TB) remains a significant public health problem in Indonesia, including in Pekanbaru City, which has shown a relatively high trend of cases in recent years. TB cases in Pekanbaru remain high, with 1,685 cases in 2024 and 1,616 cases in 2025. In the working area of Karya Wanita Public Health Center, there were 58 cases, with slum areas accounting for 8.57%. This study aimed to analyze the relationship between home environmental conditions, socioeconomic factors, behavior, and settlement conditions with the incidence of tuberculosis in the working area of the Karya Wanita Public Health Center, Pekanbaru City. This study employed a quantitative analytical approach with a case-control study design. The research was conducted in the working area of the Karya Wanita Public Health Center, Pekanbaru City, from February to March 2026. The total sample consisted of 174 respondents, including 58 TB cases and 116 non-TB controls. Data were collected through interviews using questionnaires and observations of housing conditions. Data analysis was performed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using logistic regression. The results showed that, in the multivariate analysis, variables significantly associated with TB incidence were house ventilation (p=0.040; OR=5.929), residential density (p=0.047; OR=4.754), type of floor (p=0.044; OR=9.707), income (p<0.001; OR=41.207), and settlement conditions (p=0.048; OR=0.164). Income was identified as the most dominant factor associated with TB incidence. Meanwhile, lighting, humidity, mask-wearing habits, education, and occupation were not statistically significant but were retained in the model as confounding variables. The logistic regression model produced a Nagelkerke R Square value of 0.773, indicating that the variables included in the model explained 77.3% of the variation in TB incidence. The study concludes that home environmental conditions and socioeconomic factors, particularly income, play an important role in the occurrence of tuberculosis. TB control efforts should focus on improving housing environmental